Compatibility and stability of hyoscine n-butyl bromide and furosemide admixtures for use in palliative care - Bosch-Ojeda, Catalina; Espinosa Bosch, María; Sánchez-Rojas, María Fuensanta (My University, 2015)
In order to avoid separate injections, admixtures of drugs are frequently used in palliative care settings. There are different factors that can influence the compatibility and stability of the mixture: drug type, concentration, solvent, container, temperature and light. There are some mixtures of drugs with proven stability, but there is lack of evidence about the stability and compatibility of the combination of hyoscine N-butyl bromide and furosemide.
Keywords: Química analítica; Furosemide; Hyoscine N-butyl bromide; Stability; Compatibility; Elastomeric infusor